Antibacterial Activity of Beluntas (Pluchea indica L.) Leaves Extract using Different Extraction Methods - Kinanti Ayu Puji Lestari; Putri Priliawati Pranoto; Sofiyah Sofiyah; Majidah Musyirah; Faizatin Isnaini Pratiwi (Universitas Negeri Surabaya, 2020)
Escherichia coli and Bacillus subtilis are bacteria that cause disease in the digestive tract. Pluchea indica L. had the pharmacological activity of antiseptic power against bacteria that cause digestive tract infections because of contained antibacterial compounds. The study on the comparison of extraction methods will enable the public to choose a better extraction method to use as an antibacterial agent. This study aimed to identify the content of antibacterial compounds in Pluche indica L. and to determine the antibacterial ability of Pluche indica L. extract using maceration, percolation, and soxhletation methods. The results showed that Pluchea indica L. contains flavonoids, alkaloids, saponins, and tannins. The highest diameter inhibition of Escherichia coli and Bacillus subtilis was obtained from Pluchea indica L. leaves extract extracted by using the Soxhletation method.